The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1017/s0021932019000683
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of undernutrition in Bangladeshi children

Abstract: Child undernutrition is a major public health problem throughout the world, particularly in developing countries. The main objective of this study was to identify the risk factors for acute undernutrition among under-5 children in Bangladesh. Data were taken from the nationally representative Bangladesh Demographic Health and Survey conducted in 2014. The study sample comprised 7131 under-5 children. Of these, 4.6% were found to be severely wasted (Z-score < −3.0), 11.1% moderately wasted (−3.0≤Z-score <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
7
14
0
3
Order By: Relevance
“…In contrast, CISAF uses conventional nutritional indicators' aggregate values to estimate the overall burden of severe malnutrition, thus provide a more convincing estimation of the proportion of malnourished children in the population [10]. Our nding of a higher prevalence of severe under-5 malnutrition in rural areas concurs with previous research [20,21,22,23]. Several studies have also reported a higher prevalence of severe under-5 malnutrition in urban areas in Bangladesh with limited geographical coverage [24,25,26].…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, CISAF uses conventional nutritional indicators' aggregate values to estimate the overall burden of severe malnutrition, thus provide a more convincing estimation of the proportion of malnourished children in the population [10]. Our nding of a higher prevalence of severe under-5 malnutrition in rural areas concurs with previous research [20,21,22,23]. Several studies have also reported a higher prevalence of severe under-5 malnutrition in urban areas in Bangladesh with limited geographical coverage [24,25,26].…”
Section: Discussionsupporting
confidence: 85%
“…This findings are consistent with findings from Tanzania by Mshida et al [22], and from Onitsa South eastern Nigeria by Ndukwu et al [23]. The pathophysiology of undernutrition due to prolong influence of unhygienic environmental factors via environmental enteropathy (EE) or Environmental Enteric Dysfunction (EED) and which triggers mal-absorption has been adequately described [12,[24][25][26]. This aptly explains the association between underweight and the WASH factors.…”
Section: Underweight (Malnutrition) and Wash Factorssupporting
confidence: 89%
“…However, the possibility of the shift towards more wasting in urban settings of low and middle-income countries was predicted in the UNICEF publication Innocenti Digest number 10 in 2002 [79]. Under five children living in informal settlements in large cities are often exposed to very precarious conditions that can lead to poor health status, including poor nutrition status [79,80]. The presence of such informal settlements should be a trigger for including urban setting in all strategies to tackle undernutrition.…”
Section: Risk Factors For Wastingmentioning
confidence: 99%